Arterial hypertension in Turner syndrome: a review of the literature and a practical approach for diagnosis and treatment. Issue 7 (July 2015) - De Groote, Katya; Demulier, Laurent; De Backer, Julie; De Wolf, Daniel; De Schepper, Jean; T'sjoen, Guy; De Backer, Tine
Abstract : Turner syndrome is a rare chromosomal disorder with complete or partial absence of one X chromosome that only occurs in women. Clinical presentation is variable, but congenital and acquired cardiovascular diseases are frequently associated diseases that add significantly to the increased morbidity and mortality in Turner syndrome patients. Arterial hypertension is reported in 13–58% of adult Turner syndrome patients and confers an increased risk for stroke and aortic dissection. Hypertension can be present from childhood on and is reported in one-quarter of the paediatric Turner syndrome patients. This article reviews the prevalence and cause of arterial hypertension in Turner syndrome and describes the relationship between blood pressure, aortic dilation and increased cardiovascular risk. We compare current treatment strategies and also propose an integrated practical approach for the diagnosis and treatment of hypertension in Turner syndrome applicable in daily practice.